2021
DOI: 10.1111/cas.14826
|View full text |Cite
|
Sign up to set email alerts
|

Capmatinib in Japanese patients with MET exon 14 skipping–mutated or MET‐amplified advanced NSCLC: GEOMETRY mono‐1 study

Abstract: MET mutations leading to exon 14 skipping (METΔex14) are strong molecular drivers for non–small‐cell lung cancer (NSCLC). Capmatinib is a highly potent, selective oral MET inhibitor that showed clinically meaningful efficacy and a manageable safety profile in a global phase II study (GEOMETRY mono‐1, NCT02414139) in patients with advanced METΔex14‐mutated/MET‐amplified NSCLC. We report results of preplanned analyses of 45 Japanese patients according to MET status (METΔex14‐mutated or MET‐amplified) and line of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
2
23
0
1
Order By: Relevance
“…Although in a different patient population, with EGFR -mutated NSCLC, preliminary data suggest savolitinib in combination with osimertinib, a third-generation EGFR tyrosine kinase inhibitor, is well tolerated in Japanese patients ( 27 ). In Japanese patients who received the selective MET inhibitor capmatinib for MET exon 14 skipping advanced NSCLC in the GEOMETRY mono-1 study, ORRs of 50.0% and 36.4% were observed for treatment-naïve ( n = 2) and previously treated ( n = 11) Japanese patients, respectively ( 28 ). The efficacy of tepotinib in Japanese patients presented here is consistent with previously reported outcomes for the overall VISION study population ( 15 ), in which tepotinib demonstrated consistent efficacy irrespective of the number of prior lines of therapy received.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in a different patient population, with EGFR -mutated NSCLC, preliminary data suggest savolitinib in combination with osimertinib, a third-generation EGFR tyrosine kinase inhibitor, is well tolerated in Japanese patients ( 27 ). In Japanese patients who received the selective MET inhibitor capmatinib for MET exon 14 skipping advanced NSCLC in the GEOMETRY mono-1 study, ORRs of 50.0% and 36.4% were observed for treatment-naïve ( n = 2) and previously treated ( n = 11) Japanese patients, respectively ( 28 ). The efficacy of tepotinib in Japanese patients presented here is consistent with previously reported outcomes for the overall VISION study population ( 15 ), in which tepotinib demonstrated consistent efficacy irrespective of the number of prior lines of therapy received.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, blood creatinine increase was the most common treatment-related AE experienced in Japanese patients (63.2%, all Grade 1–2). Blood creatinine increase was also the most common treatment-related AE in Japanese patients in the GEOMETRY mono-1 study of capmatinib ( 28 ). Based on non-clinical studies, increases in creatinine may reflect direct inhibitory effects on renal tubular transporters ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Capmatinib, another oral, ATP-competitive selective type Ib MET inhibitor, was first approved in 2020 in the US for treatment of METex14 skipping NSCLC, 9,12,13 based upon data from the Phase II GEOMETRY mono-1 study (Table 1; NCT02414139). [26][27][28] In the GEOMETRY mono-1 study, 364 patients with either METex14 skipping NSCLC or MET amplification were enrolled and treated with 400 mg capmatinib tablets twice daily for a 21day cycle (the recommended Phase II dose [RP2D], either with or without fasting restrictions; a maximum of two dose reductions were permitted (to 300 mg twice daily, then 200 mg twice daily). 26,27 Across the study, 151 patients with METex14 skipping NSCLC were treated and 128 analyzed for efficacy.…”
Section: Capmatinibmentioning
confidence: 99%
“…Raised creatinine is typically associated with renal impairment; however, MET TKIs are known to inhibit creatinine transporters, causing creatinine levels to rise by approximately 20% to 25%. 28,59 In patients with ALK-rearranged NSCLC treated with crizotinib, increased creatinine levels have been reported as being approximately 25%, 40,41 and retrospective data suggest that crizotinib can decrease creatinine-driven eGFR by 24% over the first 12 weeks of treatment (p< 0.0001). 41 Once treatment was stopped, eGFR recovered to baseline levels or above in 56% of patients; the remainder recovered to within 84% to 97% of their baseline eGFR.…”
Section: Increased Creatininementioning
confidence: 99%
See 1 more Smart Citation